The English Teachers’ Perceptions Using English Child-Friendly Songs in Teaching English for Young Leaners - Alamsyah (International Conference on Elementary Education, 2024)
English Child-friendly songs as teaching media for young learners are a type of learning material that utilizes song lyric as a tool to teach English skill. This research aims to explore teachers’ perceptions in using English child-friendly song in teaching English to young learners. The method of this study used descriptive method (case study) and this study used Interviews as instrument to collect the data. The instrument were involved with two novice teachers and one senior teacher who use English child-friendly songs in teaching English to young learners in the classrooms. The result showed that the teachers informed positive views of using the songs when teaching English to young learners such as helping young learners increasing young learners’ vocabulary mastery, and increasing young learners’ memory, and increasing young learners’ overall enjoyment of learning English in the classroom. This research concluded that the using of English child-friendly song is effective to enhance learning quality in teaching English to young learning.